Rharodesmus Schubart, 1960—a tropical element in the North African fauna: a new species from Tunisia and notes on the family Pyrgodesmidae (Diplopoda: Polydesmida) - Akkari, Nesrine; Enghoff, Henrik (Zootaxa, 2011)
The family Pyrgodesmidae and the genus Rharodesmus Schubart, 1960 are recorded for the first time from Tunisia. A new species, Rharodesmus tabarkensis, is described using scanning electron microscopy, and its membership in the genus and the family is discussed. Notes on west Palaearctic pyrgodesmid species are provided with considerations on the family Pyrgodesmidae.